Guanosine regulates adenosine levels in the kidney. Issue 5 (May 2014) - Jackson, Edwin K.; Cheng, Dongmei; Mi, Zaichuan; Gillespie, Delbert G.
Abstract In cell culture, extracellular guanosine increases extracellular adenosine by attenuating the disposition of extracellular adenosine (American Journal of Physiology – Cell Physiology 304: C406–C421, 2013). The goal of this investigation was to determine whether this "guanosine–adenosine mechanism" is operative in an intact organ. Twenty‐seven isolated, perfused mouse kidneys were subjected to metabolic poisons (iodoacetate plus 2, 4‐dinitrophenol) to cause energy depletion and thereby stimulate renal adenosine production. Adenosine levels in the renal venous perfusate increased from a baseline of 36 ± 8 to 499 ± 96, 258 ± 50, and 71 ± 13 nmol/L at 15, 30, and 60 min, respectively, after administering metabolic poisons (% of basal; 1366 ± 229, 715 ± 128, and 206 ± 33, respectively). Changes in renal venous levels of guanosine closely mirrored the time course of changes in adenosine: baseline of 15 ± 2 to 157 ± 13, 121 ± 8, and 50 ± 5 nmol/L at 15, 30, and 60 min, respectively (% of basal; 1132 ± 104, 871 ± 59, and 400 ± 51, respectively). Freeze‐clamp experiments in 12 kidneys confirmed that metabolic poisons increased kidney tissue levels of adenosine and guanosine. In eight additional kidneys, we examined the ability of guanosine to reduce the renal clearance of exogenous adenosine; and these experiments revealed that guanosine significantly decreased the renal extraction of adenosine. Because guanosine is metabolized by purine nucleoside phosphorylase (PNPase), in another set of 16 kidneys we examined the effects of 8‐aminoguanine (PNPase inhibitor) on renal venous levels of adenosine and inosine (adenosine metabolite). Kidneys treated with 8‐aminoguanine showed a more robust increase in both adenosine and inosine in response to metabolic poisons. We conclude that in the intact kidney, guanosine regulates adenosine levels.